Impact of vaccine mandates and removals on COVID-19 vaccine uptake in Australia and international comparators: a study protocol - Annette K Regan; Bette Liu; Christopher C Blyth; Francesco Paolucci; Kristine Macartney; Katie Attwell; Huong Le; Frank H Beard; Hannah Catherine Moore; Aregawi Gebremedhin Gebremariam; Mesfin Genie (BMJ Open)
Background Vaccination against SARS-CoV-2 was a crucial public health measure during the COVID-19 pandemic. Among the multiple strategies developed to increase vaccine uptake, governments often employed vaccine mandates. However, little evidence exists globally about the impact of these mandates and their subsequent removal on vaccine uptake, including in Australia, France, Italy and the USA. The aim of this study is to provide a protocol to evaluate and quantify the impact of COVID-19 vaccine mandates and removals on vaccine uptake in these countries, with a specific focus on comparing Australian policies with those from Europe and the USA. Actualising the work outlined in this protocol will help to provide policy and technical guidance for future pandemic preparedness and routine immunisation programmes.Methods and analysis This protocol outlines a retrospective study using existing data sources including Australian Immunisation Register-Person Level Integrated Data Asset for Australia and publicly available data for France, Italy and California (USA). Causal inference methods such as interrupted time series, regression discontinuity design, difference-in-differences, matching and synthetic control will be employed to assess the estimated effects of vaccine mandates and removals on vaccine uptake.Ethics and dissemination The University of Newcastle’s human research ethics committee has approved the study (reference number: H-2024-0160). Peer-reviewed papers will be submitted, and results will be presented at public health, immunisation and health economic conferences nationally and internationally. A lay summary will be published on the MandEval website.